If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(5y+-7)=6
We move all terms to the left:
-3(5y+-7)-(6)=0
We add all the numbers together, and all the variables
-3(5y-7)-6=0
We multiply parentheses
-15y+21-6=0
We add all the numbers together, and all the variables
-15y+15=0
We move all terms containing y to the left, all other terms to the right
-15y=-15
y=-15/-15
y=1
| -64+16x²=0 | | 2x+6+38=5 | | -5n=3n=-10 | | -1,316+188m=0 | | 2x-12=8-4x | | 6x+4-2=10+ | | 0=-0.0444x^2+1.3333x | | 134=x+x+x-5+x-5 | | -9x-13+11x+6=11x-9x+13-6 | | 1+r9=0 | | 21m^2+17m-30=0 | | 3*x-2*x=-4 | | 6r=×5r | | 1/2•x/4=3/8 | | n/2+6=9 | | 5x+16=6x-9 | | 2/9x+1/5x=38 | | 12x-5=-3x+25 | | 18=2(4+x) | | -b+3=4 | | n2+ 6= 9 | | n/2+ 6= 9 | | -29=-v/4 | | 4x+3=16.24 | | -6+3j=-9 | | 3^2+9x=0 | | 5(3x+7)=20-2(x1) | | -29=v/4 | | 100x-x=21 | | -w/3=-34 | | 7.25t+8=18.5t+17 | | -0.63x+0.42x=5.8 |